Dynamics of water reallocation and cost implications in the transboundary setting of Ferghana Province. Issue 1 (2nd January 2016) - Wegerich, Kai; Soliev, Ilkhom; Akramova, Indira
Abstract : While in the international literature water sharing in the Syr Darya Basin per past agreements is widely portrayed as most benefiting Uzbekistan, here the dynamics of water allocation within small transboundary tributaries in Ferghana Province show Uzbekistan as benefiting least. The case study highlights that water allocation for Uzbekistan within the tributaries has decreased over the years. Uzbekistan's approach to compensate for the reduced allocations by means of other water sources has had large long-term cost implications for irrigated agriculture as well as the irrigation bureaucracy. This article contributes to the international debate on benefit sharing in transboundary rivers. The article highlights that costs should be incorporated into the benefit-sharing approach, and therefore the focus on benefit sharing alone is misguiding riparian states. Furthermore, the article raises the need to reevaluate benefits, since perceptions of potential benefits change over time.